Design of Mathematic Learning Module Based on Ethnomathematicsusing Inquiry Method to Improve Mathematical Connection Ability Students of Class VII - Azzatia, Syah Fathi; Suparman (Jurnal Pendidikan Bitara UPSI, 2019)
Mathematical connections are the ability to link between topics in mathematics, associate mathematics with other sciences, and with daily life. Mathematical connection day is one of the abilities that are the goal of learning mathematics. Teaching materials or modules that are not compatible with mathematical connection capabilities can support learning objectives. Ethnomathematics is one that used in learning mathematics through cultural media that is around students. The inquiry is a way of learning to find solutions in a critical, analytical, and scientific method by using steps to conclusions because facts support them. So, getting ethnomathematics and inquiry combined can improve students’ mathematical connection abilities. This study aims to design teaching materials consisting of ethnomathematics-based mathematical modules using inquiry methods to improve mathematical connections. This research is a type of ADDIE development research. The procedure of this research includes analysis, design, development, implementation, and evaluation. This research is limited to the design stage. The subjects of this study consisted of teachers and students from MTs Al Muhsin II Kasihan in Indonesia. Data collection instruments include observation guidelines, interview guidelines, and documentation sheets. Observation guidelines are used to see the characteristics of students’ mathematical connections. Interview guides are used to determine the teaching material needs of teachers. A documentation sheet is used to obtain data on curriculum implementation in schools. Qualitative-quantitative techniques analyzed data. This research resulted in ethnomathematics are based on module design according to student’s needs. This module is designed to improve students’ mathematical connection skills. The results of expert validation on the design of modules get an average value of 4 and are declared valid and can proceed to the next stage.